2018
DOI: 10.1038/s41467-018-05526-5
|View full text |Cite
|
Sign up to set email alerts
|

Social interactions impact on the dopaminergic system and drive individuality

Abstract: Individuality is a striking feature of animal behavior. Individual animals differ in traits and preferences which shape their interactions and their prospects for survival. However, the mechanisms underlying behavioral individuation are poorly understood and are generally considered to be genetic-based. Here, we devised a large environment, Souris City, in which mice live continuously in large groups. We observed the emergence of individual differences in social behavior, activity levels, and cognitive traits,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 53 publications
2
76
0
Order By: Relevance
“…Similar experiments with a D1 receptor antagonist facilitated or did not modify social dominance in mice and monkeys (Yamaguchi et al 2017b) whereas local injection into the NAcc of an agonist increased dominance in rats (Van der Kooij 2018). Interestingly, changes in VTA dopamine cells activity is observed during the emergence of behavioral categories occurring within groups of dozens of mice living in complex semi-naturalistic environments (Torquet et al, 2018). It will be interesting to study social ranking between these categories using precedence test such as the tube test.…”
Section: Discussionmentioning
confidence: 99%
“…Similar experiments with a D1 receptor antagonist facilitated or did not modify social dominance in mice and monkeys (Yamaguchi et al 2017b) whereas local injection into the NAcc of an agonist increased dominance in rats (Van der Kooij 2018). Interestingly, changes in VTA dopamine cells activity is observed during the emergence of behavioral categories occurring within groups of dozens of mice living in complex semi-naturalistic environments (Torquet et al, 2018). It will be interesting to study social ranking between these categories using precedence test such as the tube test.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis for the heterogeneity we observed in our animal model could be of epigenetic and/or environmental origin. It has been shown for example that phenotypic variability can emerge from variations in epigenetic regulation (59,(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…As for OCD patients, we attempted to determine a similar heterogeneity in the KO mice. Indeed, some innovative studies have found evidence for inter-individual variability of cognitive traits in animal models (58,59), pointing out it is a necessary consideration for animal studies. To do so, we performed a two-step cluster analysis which identified two clusters within the KO mice with a silhouette measure of 0.6, indicating a good solution.…”
Section: Distinct Subgroups Of Ocd Patients and Ko Mice Exhibit A Behmentioning
confidence: 99%
“…Thus, our current results suggest that the strength of intrinsic hippocampal-cortical connectivity is a potential candidate for the modulation of goal-directed behavior in social groups. Social relationships can shape individual behavior and affect decision-making [38]. Although dominance hierarchy emerges from recurrent social interactions, it causally results from the synaptic efficacy of excitatory transmission in the mPFC [9].…”
Section: Discussionmentioning
confidence: 99%